Review of Flexible Temperature Sensing Networks for Wearable Physiological Monitoring - Li, Qiao; Zhang, Li‐Na; Tao, Xiao‐Ming; Ding, Xin (Advanced healthcare materials, 2017)
Physiological temperature varies temporally and spatially. Accurate and real‐time detection of localized temperature changes in biological tissues regardless of large deformation is crucial to understand thermal principle of homeostasis, to assess sophisticated health conditions, and further to offer possibilities of building a smart healthcare and medical system. Additionally, continuous temperature mapping in flexible and stretchable formats opens up many other potential areas, such as artificially electronic skins and reflection of emotional changes. This review exploits a comprehensive investigation onto recent advances in flexible temperature sensors, stretchable sensor networks, and platforms constructed in soft and compliant formats for wearable physiological monitoring. The most recent examples of flexible temperature sensors are first discussed regarding to their materials, structures, electrical and mechanical properties; temperature sensing network technologies in new materials and structural designs are then presented based on platforms comprised of multiple physical sensors and stretchable electronics. Finally, wearable applications of the sensing network are described, such as detection of human activities, monitoring of health conditions, and emotion‐related bodily sensations. Conclusions are made with emphasis on critical issues and new trends in the field of wearable temperature sensor network technologies. Accurate and real‐time detection of localized temperature changes in biological tissues regardless of large deformation is crucial to understand thermal principle of homeostasis and to assess sophisticated health conditions. This review exploits recent advances in flexible temperature sensors, stretchable sensor networks, and platforms constructed in soft and compliant formats for wearable physiological monitoring.